Children in Street Situations, Their Determinants, Survival and Strategies. Case of the City of Bujumbura - Ladislas, Gahungu; Leandre, Simbananiye; Fabienne, Glowacz (European Scientific Journal, ESJ, 2024)
The aim of this article is to establish the link between the determinants of street life and the violence experienced by children and their survival in the city of Bujumbura. To gather the experiences of our interviewees, we used a life history with semi-structured interviews, and direct and indirect observation. To identify emerging themes, we carried out a thematic analysis of the interview content. Analysis of the empirical corpus of 43 street children reveals nine determinants at the root of the street child phenomenon, grouped into two categories, namely environmental and personal and interpersonal determinants centered on parent-child relationships. There are also determinants linked to educational styles that interact with the child’s behavior. The stepmother is often perceived by children and their in-laws as a "ferocious animal’’, even in the absence of a negative upbringing. When family life fails, the street becomes an alternative. Exposed to all forms of violence, child victims become violent, and the cycle of violence is fueled. Stories of life on the streets show that every child has his/ her problems. Previous results show that the determinants of street life are multifactorial and have causal links that are part of a cyclical context of violence. Our results go further, proving that in addition to environmental determinants, there are also personal and interpersonal ones. Combating this phenomenon requires preventive action at the primary, secondary and tertiary levels: preventing the development of the problem, intervening early and, finally, treating the consequences and reintegrating the children.